Flexible carbon-based substrate self-supporting nano composite material electrode and preparation method thereof

By compositeing heterogeneous atom doping carbon materials and nanotransition metal compound particles on a flexible carbon-based substrate, the problems of uneven coating, material decomposition and complex process in electrode preparation are solved, and electrode materials with high stability and high efficiency charge transport are achieved.

CN119889944APending Publication Date: 2025-04-25ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510032084.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the existing electrode preparation process, uneven coating leads to uneven distribution of active materials, affecting electrode performance and stability; electrode materials may decompose or fail at high temperatures, affecting long-term stability; the coating process is complex, difficult to operate, and time-consuming.

Method used

A one-step high-temperature carbonization method is used to composite heteroatom-doped carbon materials and nanotransition metal compound particles on a flexible carbon-based substrate, and the stability and charge transfer efficiency of the electrode are improved through covalent cross-linking interface and anchoring transition metal nanoparticles.

Benefits of technology

It effectively reduces the internal resistance of the electrode, improves the stability and charge transfer efficiency of functional nanotransition metal compounds in the electrochemical process, simplifies the preparation process, and improves the simplicity of operation and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889944A_ABST
    Figure CN119889944A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a flexible carbon-based substrate self-supporting nanocomposite electrode and a preparation method thereof. The method comprises the following steps: S1, preparing a doping solution by using ethanol soluble resin, a doping precursor and transition metal salt; s2, treating a flexible carbon-based substrate by using the obtained doping solution, and loading resin, a doping precursor and transition metal ions on the flexible carbon-based substrate; s3, performing heat treatment on the flexible carbon-based substrate treated by the doping solution at a set temperature, uniformly coating the carbon fiber surface of the flexible carbon-based substrate with heteroatom-doped porous carbon, and anchoring discretely distributed transition metal nanoparticles; s4, the transition metal nanoparticles on the flexible carbon-based substrate are subjected to a combination reaction under set conditions, and the transition metal nanoparticles are converted into a transition metal compound; the flexible carbon-based substrate self-supporting nano composite material electrode doped with the heteroatom-doped carbon material and the nano transition metal compound is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical technology, and in particular relates to a flexible carbon-based substrate self-supporting nanocomposite material electrode and a preparation method thereof. Background Art

[0002] In the preparation of supercapacitor electrodes, water electrolysis catalyst electrodes and battery electrodes, compounding the electrode active material powder with the current collector is one of the essential processes. Common methods include: coating, spraying, tableting and electrodeposition. The typical process flow includes the following steps: preparing the powder of the electrode active material, mixing the powder with a conductive agent and a binder to form an electrode slurry or mixed powder, coating the electrode slurry on the current collector, and finally drying and pressing to form a finished electrode.

[0003] However, there are the following problems in the existing technology:

[0004] Due to the complexity of the coating process, it is difficult to obtain a completely uniform electrode coating. Uneven coating can lead to uneven distribution of active materials in the electrode, affecting the performance and stability of the electrode.

[0005] During the mixing process of the electrode active material powder, the conductive agent and the binder, the powder particles tend to aggregate, resulting in large particles or agglomerates in the electrode, which reduces the specific surface area and conductivity of the electrode.

[0006] Binders can improve mechanical strength and adhesion, but they will affect the conductivity and ion transport properties of the electrode. Moreover, binders may decompose or fail at high temperatures, affecting the long-term stability of the electrode.

[0007] During long-term cycling, the interfacial stability between the electrode material and the current collector is easily affected by problems such as impedance increase and delamination, resulting in electrode performance degradation;

[0008] The coating process is complex, requires multiple steps, is difficult to operate, and takes a long time. Summary of the invention

[0009] In view of this, on the one hand, some embodiments disclose a method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode, comprising the steps of:

[0010] S1. Preparing a doping solution using an ethanol-soluble resin, a doping precursor and a transition metal salt; the doping precursor includes a combination of one or more of a phosphorus dopant, a nitrogen dopant or a sulfur dopant; the transition metal salt includes one or a combination of any two of Fe, Co, Ni, Mn, W, Mo or V salts;

[0011] S2, treating the flexible carbon-based substrate with the obtained doping solution to load the resin, doping precursor and transition metal ions on the flexible carbon-based substrate;

[0012] S3, heat-treating the flexible carbon-based substrate treated with the doping solution at a set temperature, uniformly coating the heterogeneous atom-doped porous carbon on the carbon fiber surface of the flexible carbon-based substrate, and anchoring discretely distributed transition metal nanoparticles;

[0013] S4. The transition metal nanoparticles on the flexible carbon-based substrate undergo a chemical reaction under set conditions, and the transition metal nanoparticles are converted into transition metal compounds; a flexible carbon-based substrate self-supporting nanocomposite electrode doped with heteroatom-doped carbon materials and nano transition metal compounds is obtained; wherein the chemical reaction of the transition metal nanoparticles includes sulfurization reaction, nitridation reaction, and phosphiding reaction.

[0014] In some embodiments, the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in step S1 specifically comprises:

[0015] Mixing an ethanol-soluble resin, a doping precursor and a transition metal salt in a mass ratio of 1-4:0.25-1.0:1-2, and dissolving them in ethanol;

[0016] Stir for 0.5 to 3 hours to obtain a uniform doping solution.

[0017] In some embodiments of the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode, in step S2, the flexible carbon-based substrate is first pretreated, specifically comprising:

[0018] The flexible carbon-based substrate was ultrasonically washed in anhydrous ethanol and then dried under vacuum.

[0019] In some embodiments of the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode, step S2 specifically includes:

[0020] The flexible carbon-based substrate was immersed in the doping solution and ultrasonically treated for 1 to 2 h;

[0021] The flexible carbon-based substrate impregnated with the doping solution is blown dry in an oven for 3 minutes until the flexible carbon-based substrate is solidified;

[0022] Then blow dry at 60℃ for 1 to 3 hours.

[0023] In the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in some embodiments, the heat treatment of the flexible carbon-based substrate after being treated with the doping solution in step S3 comprises:

[0024] The flexible carbon-based substrate treated with the doping solution is placed in an atmosphere furnace, heated to 600-900° C. at 5-10° C. / min in a nitrogen or argon environment, kept warm for 1-2 hours, and cooled to room temperature.

[0025] In the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in some embodiments, step S3 further comprises:

[0026] The heat-treated flexible carbon-based substrate is immersed in deionized water for washing;

[0027] The washed flexible carbon-based substrate is dried in a vacuum drying oven at 120° C. for 12 h to obtain a flexible carbon-based substrate with heteroatom-doped porous carbon uniformly coated on the carbon fiber surface and discretely distributed transition metal nanoparticles anchored thereon.

[0028] In the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in some embodiments, in step S4, the chemical reaction includes:

[0029] Placing a chemical reaction reagent and a heat-treated flexible carbon-based substrate in a reaction boat, and performing a chemical reaction under a nitrogen or argon atmosphere;

[0030] The flexible carbon-based substrate after the chemical reaction is immersed in deionized water and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite material electrode composited with heterogeneous atom-doped carbon material and nano transition metal compound.

[0031] Some embodiments disclose a method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode, wherein the chemical reaction reagents used for the sulfurization reaction include sublimated sulfur and thiourea; the chemical reaction reagents used for the nitridation reaction include triazine derivatives and urea; the chemical reaction reagents used for the phosphation reaction include phytic acid or sodium phosphite; and the molar ratio of the chemical reaction reagents to the transition metal nanoparticles is 3 to 5:1.

[0032] In some embodiments of the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode, the ethanol-soluble resin includes epoxy resin and phenolic resin.

[0033] On the other hand, some embodiments disclose a flexible carbon-based substrate self-supporting nanocomposite electrode obtained by a method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode.

[0034] The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in an embodiment of the present invention adopts a one-step high-temperature carbonization method to composite a composite electrode in which heterogeneous atom-doped carbon material and nano transition metal compound particles are uniformly distributed on a flexible carbon-based substrate, so that the doped carbon material in the electrode material forms a covalent cross-linking interface with the carbon substrate, and at the same time, the nano transition metal compound particles are anchored on the carbon fiber surface of the carbon-based substrate to prevent them from growing, thereby effectively reducing the electrode internal resistance caused by the physical contact between the electrode active material and the current collector, and improving the stability and charge transfer efficiency of the functional nano transition metal compound in the electrochemical process; the method is simple and easy to implement, and has good application prospects in the field of composite material electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the product of Example 1 after high temperature treatment at 800°C;

[0036] Figure 2 This is a SEM image of the product of Example 1 after high temperature treatment at 800°C and phosphating treatment at 350°C;

[0037] Figure 3 is the XRD pattern of the composite electrode sample of Example 1;

[0038] Figure 4 This is the LSV polarization curve of the composite electrode sample of Example 1 in an alkaline environment;

[0039] Figure 5 This is a SEM image of the product obtained after high temperature treatment at 700°C in Example 2;

[0040] Figure 6 This is the LSV polarization curve of the composite material electrode of Example 2 in an alkaline environment.

[0041] Figure 7 This is the XRD pattern of the composite material electrode sample of Example 3;

[0042] Figure 8 This is the LSV polarization curve of the composite electrode sample of Example 3 in an alkaline environment;

[0043] Fig. 9 The SEM image and mapping image of the product obtained by high temperature treatment at 800°C in Example 4;

[0044] Fig.10 is the XRD pattern of the composite electrode sample of Example 4;

[0045] Fig.11 This is the LSV polarization curve of the composite material electrode sample of Example 4 in an alkaline environment. DETAILED DESCRIPTION

[0046] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.

[0047] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.

[0048] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​clearly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Therefore, independent values ​​such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.

[0049] In this document, including in the claims, transitional words such as "comprises," "includes," "with," "having," "containing," "involving," "accommodating," etc. are understood to be open-ended, i.e., meaning "including but not limited to." Only the transitional words "consisting of" and "composed of" are closed transitional words.

[0050] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.

[0051] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention may be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.

[0052] In some embodiments, the method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode comprises the steps of:

[0053] S1. A doping solution is prepared using an ethanol-soluble resin, a doping precursor and a transition metal salt; the doping precursor includes a combination of one or more of a phosphorus dopant, a nitrogen dopant or a sulfur dopant; the transition metal salt includes one or a combination of any two of Fe, Co, Ni, Mn, W, Mo or V salts; the ethanol-soluble resin includes an epoxy resin and a phenolic resin; in a subsequent heat treatment process, the doping precursor and the resin are carbonized at high temperature and in situ converted into heterogeneous atom-doped porous carbon, which is coated on the surface of the carbon fiber of the carbon-based substrate, and at the same time, the transition metal salt is in situ converted into transition metal elemental nanoparticles and anchored on the surface of the carbon fiber; the heterogeneous atom refers to a phosphorus atom, a nitrogen atom or a sulfur atom;

[0054] In some embodiments, an ethanol-soluble resin, a doping precursor, and a transition metal salt are mixed in a mass ratio of 1 to 4: 0.25 to 1.0: 1 to 2, and dissolved in ethanol; stirred for 0.5 to 3 hours to obtain a uniform doping solution;

[0055] S2. Using the obtained doping solution to treat a flexible carbon-based substrate, the resin, the doping precursor and the transition metal ions are loaded on the flexible carbon-based substrate; the flexible carbon-based substrate includes carbon fiber cloth and carbon fiber paper;

[0056] In some embodiments, before treating the flexible carbon-based substrate with the doping solution, the flexible carbon-based substrate is pretreated, specifically comprising: ultrasonically washing the flexible carbon-based substrate in anhydrous ethanol and then drying it in a vacuum;

[0057] In some embodiments, treating the flexible carbon-based substrate with a doping solution specifically includes: immersing the flexible carbon-based substrate in a doping solution and ultrasonically treating the flexible carbon-based substrate for 1 to 2 hours; blowing the flexible carbon-based substrate immersed in the doping solution in an oven for 3 minutes until the flexible carbon-based substrate is solidified; and then blowing the flexible carbon-based substrate at 60° C. for 1 to 3 hours;

[0058] S3, heat-treating the flexible carbon-based substrate treated with the doping solution at a set temperature, carbonizing the doping precursor and the ethanol-soluble resin to generate heterogeneous atom-doped porous carbon, and decomposing the transition metal salt to generate transition metal element particles. During the reaction, the heterogeneous atom-doped porous carbon is uniformly coated on the carbon fiber surface of the flexible carbon-based substrate, and discretely distributed transition metal nanoparticles are anchored on the carbon fiber surface;

[0059] In some embodiments, the heat treatment of the flexible carbon-based substrate after being treated with the doping solution comprises:

[0060] The flexible carbon-based substrate treated with the doping solution is placed in an atmosphere furnace, heated to 600-900° C. at 5-10° C. / min in a nitrogen or argon environment, kept warm for 1-2 hours, and cooled to room temperature.

[0061] Further, in some embodiments, the heat-treated flexible carbon-based substrate is immersed in deionized water for washing; the washed flexible carbon-based substrate is dried in a vacuum drying oven at 120° C. for 12 hours to obtain a flexible carbon-based substrate having a carbon fiber surface uniformly coated with heterogeneous atom-doped porous carbon and anchored with discretely distributed transition metal nanoparticles;

[0062] S4. The transition metal nanoparticles on the flexible carbon-based substrate undergo a chemical reaction under set conditions, and the transition metal nanoparticles are converted into transition metal compounds; a flexible carbon-based substrate self-supporting nanocomposite electrode doped with heteroatom-doped carbon materials and nano transition metal compounds is obtained; wherein the chemical reaction of the transition metal nanoparticles includes sulfurization reaction, nitridation reaction, and phosphation reaction; the chemical reaction reagents used for the sulfurization reaction include sublimated sulfur and thiourea; the chemical reaction reagents used for the nitridation reaction include triazine derivatives and urea; the chemical reaction reagents used for the phosphation reaction include phytic acid or sodium phosphite;

[0063] The chemical reactions include:

[0064] Placing a chemical reaction reagent and a heat-treated flexible carbon-based substrate in a reaction boat, and performing a chemical reaction under a nitrogen or argon atmosphere;

[0065] The flexible carbon-based substrate after the chemical reaction is immersed in deionized water and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite material electrode composited with heterogeneous atom-doped carbon material and nano transition metal compound.

[0066] Some embodiments disclose a flexible carbon-based substrate self-supporting nanocomposite electrode, which is obtained by a method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode. The electrode uses a flexible carbon-based substrate material as the material body, and the carbon fiber surface of the carbon-based substrate is composited with heterogeneous atom-doped porous carbon material and nano transition metal compound particles. The coating effect of the heterogeneous atom-doped porous carbon on the carbon fiber and the anchoring effect on the transition metal compound particles can effectively prevent the insufficient active sites caused by the agglomeration of the transition metal compound particles, reduce the internal resistance of the electrode, and improve the stability of the electrode.

[0067] In some embodiments, the flexible carbon-based self-supporting nanocomposite electrode disclosed in the present invention is used for electrochemical energy storage or electrochemical conversion process. The heterogeneous element doping of the porous carbon material can effectively increase the chemical reaction active sites of the composite electrode, improve the wetting performance of the composite electrode with the aqueous electrolyte, and increase the electrochemical reaction rate.

[0068] The technical details are further illustrated below in conjunction with embodiments.

[0069] Example 1

[0070] The method for preparing the flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in Example 1 comprises:

[0071] The carbon cloth was immersed in anhydrous ethanol and ultrasonically washed for 30 minutes to remove impurities on the surface of the carbon cloth; after being taken out, it was dried under vacuum at 120°C for 6 hours for later use;

[0072] 20 mL of anhydrous ethanol was placed in a 50 mL beaker, and then 2 g of Co(NO3)2·6H2O and 0.25 g of 1,3,5-tris(2-hydroxyethyl)cyanuric acid were added to the anhydrous ethanol to dissolve, and 1 g of phenolic resin was added to the anhydrous ethanol solution, and stirred and dissolved at room temperature for 30 min to obtain a doping solution;

[0073] The doping solution was ultrasonically treated for 40 min using a probe ultrasonic instrument to ensure that the phenolic resin and the cobalt salt were completely and evenly dispersed in the doping solution;

[0074] The carbon cloth is immersed in the dispersed doping solution and then ultrasonically treated for 1 hour to make the phenolic resin and cobalt salt solution completely and evenly adhere to the fibers of the carbon cloth;

[0075] The carbon cloth after impregnation treatment was taken out with tweezers. In order to prevent the surface morphology of the carbon cloth fiber from being damaged, the edge of the carbon cloth was fixed with tweezers and then blown dry at 60°C until the texture of the carbon cloth became hard, and then placed in an oven and continued to blow dry for 1 hour;

[0076] The completely dried carbon cloth was placed in a tubular furnace, and heated to 800°C at a rate of 5°C in an argon atmosphere, and kept at 800°C for 90 minutes for carbonization treatment. After cooling to room temperature, the carbon cloth was taken out and soaked and washed with deionized water at 60°C for 24 hours to obtain a carbon cloth loaded with metal cobalt particles.

[0077] The carbon cloth was dried and placed in a small porcelain boat, and then completely covered with 2.5 g of NaPH2O2. The small porcelain boat was then placed in a tube furnace, and heated to 350°C at a rate of 5°C / min in an argon atmosphere for phosphating reaction. The temperature was kept at 350°C for 2 h, and the metal cobalt particles were converted into cobalt phosphide particles.

[0078] After the temperature drops to room temperature, the carbon cloth after the phosphating reaction is taken out, soaked and washed with deionized water at 60°C for 24 hours, and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite electrode;

[0079] The performance test of the electrode obtained in Example 1 was carried out, and the results were as follows: Figure 1 , 2 , 3, and 4.

[0080] Figure 1 This is the SEM image of the product sample obtained after the precursor was carbonized at 800℃. It can be seen that the surface morphology of the carbon cloth fiber is obviously different; Figure 2 This is the SEM image of the carbonized product sample after phosphating. The carbon cloth fiber surface has carbon-anchored metal phosphide particles evenly distributed on the carbon fiber surface. Figure 3 This is the XRD diagram of the composite electrode sample. The product after carbonization is only Co element, and the product after phosphation is only cobalt phosphide; Figure 4 The electrochemical polarization curve of the composite electrode sample in alkaline environment, 10 mA cm -2 The overpotential can reach 96.7mV.

[0081] Example 2

[0082] The method for preparing the flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in Example 2 includes:

[0083] The carbon cloth was immersed in anhydrous ethanol and ultrasonically washed for 30 minutes to remove impurities on the surface of the carbon cloth; after being taken out, it was dried under vacuum at 120°C for 6 hours for later use;

[0084] 20 mL of anhydrous ethanol was placed in a 50 mL beaker, and then 3 g of Co(NO3)2·6H2O and 0.5 g of 1,3,5-tris(2-hydroxyethyl)cyanuric acid were added to the anhydrous ethanol to dissolve, and 4 g of phenolic resin was added to the anhydrous ethanol solution, and stirred and dissolved at room temperature for 2.5 h to obtain a doping solution;

[0085] The doping solution was ultrasonically treated for 40 min using a probe ultrasonic instrument to ensure that the phenolic resin and the cobalt salt were completely and evenly dispersed in the doping solution;

[0086] The carbon cloth is immersed in the dispersed doping solution and then ultrasonically treated for 1 hour to make the phenolic resin and cobalt salt solution completely and evenly adhere to the fibers of the carbon cloth;

[0087] The carbon cloth after impregnation treatment was taken out with tweezers. In order to prevent the surface morphology of the carbon cloth fiber from being damaged, the edge of the carbon cloth was fixed with tweezers and then blown dry at 60°C until the texture of the carbon cloth became hard, and then placed in an oven and continued to blow dry for 1 hour;

[0088] The completely dried carbon cloth was placed in a tubular furnace, and heated to 700°C at a rate of 5°C in an argon atmosphere, and kept at 700°C for 120 min for carbonization treatment. After cooling to room temperature, the carbon cloth was taken out and soaked and washed with deionized water at 60°C for 24 h to obtain a carbon cloth loaded with metal cobalt particles.

[0089] The carbon cloth was dried and placed in a small porcelain boat, and then completely covered with 2.5 g of NaPH2O2. The small porcelain boat was then placed in a tube furnace, and heated to 350°C at a rate of 5°C / min in an argon atmosphere for phosphating reaction. The temperature was kept at 350°C for 2 h, and the metal cobalt particles were converted into cobalt phosphide particles.

[0090] After the temperature drops to room temperature, the carbon cloth after the phosphating reaction is taken out, soaked and washed with deionized water at 60°C for 24 hours, and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite electrode;

[0091] The electrode obtained in Example 2 was tested for performance, and the results were as follows: Figure 5 , 6 shown.

[0092] Figure 5 This is the SEM image after high-temperature carbonization treatment at 700°C. The increase in the amount of phenolic resin will lead to an increase in carbon and the formation of carbon-coated nano-phosphide particles. Figure 6 This is the electrochemical performance curve of the composite electrode sample in an alkaline environment.

[0093] Example 3

[0094] The method for preparing the flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in Example 3 includes:

[0095] The carbon cloth was immersed in anhydrous ethanol and ultrasonically washed for 30 minutes to remove impurities on the surface of the carbon cloth; after being taken out, it was dried under vacuum at 120°C for 6 hours for later use;

[0096] 20 mL of anhydrous ethanol was placed in a 50 mL beaker, and then 2 g of NiCl2·6H2O and 0.5 g of 1,3,5-tris(2-hydroxyethyl)cyanuric acid were added to the anhydrous ethanol to dissolve, and 1 g of phenolic resin was added to the anhydrous ethanol solution, and stirred and dissolved at room temperature for 1 h to obtain a doping solution;

[0097] The doping solution was sonicated for 40 min using a probe sonicator to ensure that the phenolic resin and the nickel salt were completely and evenly dispersed in the doping solution;

[0098] The carbon cloth is immersed in the dispersed doping solution and then ultrasonically treated for 1 hour to make the phenolic resin and cobalt salt solution completely and evenly adhere to the fibers of the carbon cloth;

[0099] The carbon cloth after impregnation treatment was taken out with tweezers. In order to prevent the surface morphology of the carbon cloth fiber from being damaged, the edge of the carbon cloth was fixed with tweezers and then blown dry at 60°C until the texture of the carbon cloth became hard, and then placed in an oven and continued to blow dry for 1 hour;

[0100] The completely dried carbon cloth was placed in a tubular furnace, and heated to 800°C at a rate of 5°C in an argon atmosphere, and kept at 800°C for 90 minutes for carbonization treatment. After cooling to room temperature, the carbon cloth was taken out and soaked and washed with deionized water at 60°C for 24 hours to obtain a carbon cloth loaded with metal cobalt particles.

[0101] The carbon cloth was dried and placed in a small porcelain boat, and then completely covered with 2.5 g of NaPH2O2. The small porcelain boat was then placed in a tube furnace, and heated to 350°C at a rate of 5°C / min in an argon atmosphere for phosphating reaction. The temperature was kept at 350°C for 2 h, and the metal cobalt particles were converted into cobalt phosphide particles.

[0102] After the temperature drops to room temperature, the carbon cloth after the phosphating reaction is taken out, soaked and washed with deionized water at 60°C for 24 hours, and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite electrode;

[0103] The performance test of the electrode obtained in Example 3 was carried out, and the results are as follows: Figure 7 , 8 shown.

[0104] Figure 7 The XRD diagram of the composite electrode sample shows that the product before and after phosphating contains Ni metal, while the product after phosphating contains Ni2P and Ni 12 P5 phases of two products; Figure 8 LSV polarization curve of the composite electrode sample in alkaline environment.

[0105] Example 4

[0106] The method for preparing the flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in Example 4 includes:

[0107] The carbon cloth was immersed in anhydrous ethanol and ultrasonically washed for 30 minutes to remove impurities on the surface of the carbon cloth; after being taken out, it was vacuum dried at 120°C for 1 hour and set aside;

[0108] Take 20 mL of anhydrous ethanol and put it in a 50 mL beaker, then add 1 g of NiCl2·6H2O and 1 g of Co(NO3)2·6H2O and 0.25 g of 1,3,5-tris(2-hydroxyethyl)cyanuric acid into the anhydrous ethanol to dissolve, add 1 g of phenolic resin into the anhydrous ethanol solution, stir and dissolve at room temperature for 2.5 h to obtain a doping solution;

[0109] The doping solution was sonicated for 40 min using a probe sonicator to ensure that the phenolic resin, cobalt salt, and nickel salt were completely and evenly dispersed in the doping solution;

[0110] The carbon cloth is immersed in the dispersed doping solution and then ultrasonically treated for 1 hour to make the phenolic resin and cobalt salt solution completely and evenly adhere to the fibers of the carbon cloth;

[0111] The carbon cloth after impregnation treatment was taken out with tweezers. In order to prevent the surface morphology of the carbon cloth fiber from being damaged, the edge of the carbon cloth was fixed with tweezers and then blown dry at 60°C until the texture of the carbon cloth became hard, and then placed in an oven and continued to blow dry for 1 hour;

[0112] The completely dried carbon cloth was placed in a tubular furnace, and heated to 800°C at a rate of 5°C in an argon atmosphere, and kept at 800°C for 90 minutes for carbonization treatment. After cooling to room temperature, the carbon cloth was taken out and soaked and washed with deionized water at 60°C for 24 hours to obtain a carbon cloth loaded with metal cobalt particles.

[0113] The carbon cloth was dried and placed in a small porcelain boat, and then completely covered with 2.5 g of NaPH2O2. The small porcelain boat was then placed in a tube furnace, and heated to 350°C at a rate of 5°C / min in an argon atmosphere for phosphating reaction. The temperature was kept at 350°C for 2 h, and the metal cobalt particles were converted into cobalt phosphide particles.

[0114] After the temperature drops to room temperature, the carbon cloth after the phosphating reaction is taken out, soaked and washed with deionized water at 60°C for 24 hours, and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite electrode;

[0115] The performance test of the electrode obtained in Example 4 was carried out, and the results were as follows: Fig. 9 , 10 , as shown in 11.

[0116] Fig. 9 This is the SEM image of the product sample after high-temperature carbonization at 800℃. It can be seen that the particles on the surface of the carbon cloth fiber after phosphating are CoNi alloy; Fig.10 The XRD spectrum of the composite electrode sample is compared with the XRD patterns of the product samples before and after phosphating. The product before phosphating has Co and Ni alloy phases, while after phosphating, there is only Ni2P phase. Fig.11 The LSV polarization curve of the composite electrode sample in alkaline environment is 10 mA cm -2 The overpotential can reach 113.2mV.

[0117] The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode disclosed in an embodiment of the present invention adopts a one-step high-temperature carbonization method to composite a composite electrode in which heterogeneous atom-doped carbon material and nano transition metal compound particles are uniformly distributed on a flexible carbon-based substrate, so that the doped carbon material in the electrode material forms a covalent cross-linking interface with the carbon substrate, and at the same time, the nano transition metal compound particles are anchored on the carbon fiber surface of the carbon-based substrate to prevent them from growing, thereby effectively reducing the electrode internal resistance caused by the physical contact between the electrode active material and the current collector, and improving the stability and charge transfer efficiency of the functional nano transition metal compound in the electrochemical process; the method is simple and easy to implement, and has good application prospects in the field of composite material electrodes.

[0118] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode, characterized in that: Includes steps: S1. Preparing a doping solution using an ethanol-soluble resin, a doping precursor and a transition metal salt; the doping precursor comprises a combination of one or more of a phosphorus dopant, a nitrogen dopant or a sulfur dopant; the transition metal salt comprises one or a combination of any two of Fe, Co, Ni, Mn, W, Mo or V salts; S2, treating the flexible carbon-based substrate with the obtained doping solution to load the resin, doping precursor and transition metal ions on the flexible carbon-based substrate; S3, heat-treating the flexible carbon-based substrate treated with the doping solution at a set temperature, uniformly coating the heterogeneous atom-doped porous carbon on the carbon fiber surface of the flexible carbon-based substrate, and anchoring discretely distributed transition metal nanoparticles; S4, the transition metal nanoparticles on the flexible carbon-based substrate undergo a chemical reaction under set conditions, and the transition metal nanoparticles are converted into transition metal compounds; and a flexible carbon-based substrate self-supporting nanocomposite electrode doped with heterogeneous atom-doped carbon material and nano transition metal compounds is obtained; Among them, the chemical reactions of transition metal nanoparticles include sulfurization reaction, nitridation reaction and phosphation reaction.

2. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 1, characterized in that: Step S1 specifically includes: Mixing an ethanol-soluble resin, a doping precursor and a transition metal salt in a mass ratio of 1-4:0.25-1.0:1-2, and dissolving them in ethanol; Stir for 0.5 to 3 hours to obtain a uniform doping solution.

3. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 1, characterized in that: In step S2, the flexible carbon-based substrate is first pretreated, specifically including: The flexible carbon-based substrate was ultrasonically washed in anhydrous ethanol and then dried under vacuum.

4. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 1, characterized in that: Step S2 specifically includes: The flexible carbon-based substrate was immersed in the doping solution and ultrasonically treated for 1 to 2 h; The flexible carbon-based substrate impregnated with the doping solution is blown dry in an oven for 3 minutes until the flexible carbon-based substrate is solidified; Then blow dry at 60℃ for 1 to 3 hours.

5. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 1, characterized in that: The heat treatment of the flexible carbon-based substrate after being treated with the doping solution in step S3 includes: The flexible carbon-based substrate treated with the doping solution is placed in an atmosphere furnace, heated to 600-900° C. at 5-10° C. / min in a nitrogen or argon environment, kept warm for 1-2 hours, and cooled to room temperature.

6. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 5, characterized in that: Step S3 also includes: The heat-treated flexible carbon-based substrate is immersed in deionized water for washing; The washed flexible carbon-based substrate is dried in a vacuum drying oven at 120° C. for 12 h to obtain a flexible carbon-based substrate with heteroatom-doped porous carbon uniformly coated on the carbon fiber surface and discretely distributed transition metal nanoparticles anchored thereon.

7. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 1, characterized in that: In step S4, the chemical reaction comprises: Placing a chemical reaction reagent and a heat-treated flexible carbon-based substrate in a reaction boat, and performing a chemical reaction under a nitrogen or argon atmosphere; The flexible carbon-based substrate after the chemical reaction is immersed in deionized water and dried to obtain a flexible carbon-based substrate self-supporting nanocomposite material electrode composited with heterogeneous atom-doped carbon material and nano transition metal compound.

8. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 7, characterized in that: The chemical reaction reagents used for the sulfurization reaction include sublimated sulfur and thiourea; the chemical reaction reagents used for the nitridation reaction include triazine derivatives and urea; the chemical reaction reagents used for the phosphation reaction include phytic acid or sodium phosphite; the molar ratio of the chemical reaction reagents to the transition metal nanoparticles is 3 to 5:

1.

9. The method for preparing a flexible carbon-based substrate self-supporting nanocomposite electrode according to claim 1, characterized in that: The ethanol-soluble resin includes epoxy resin and phenolic resin.

10. A flexible carbon-based substrate self-supporting nanocomposite electrode, characterized in that: The method for preparing the flexible carbon-based substrate self-supporting nanocomposite electrode is obtained according to any one of claims 1 to 9.